Effects of Environment Sanitation on Early Neonatal Death (0-7 days) in Situbondo District - Diana Diana Farhati; Ristya Widi Endah Yani; Dewi Rokhmah (Aloha International Journal of Health Advancement (AIJHA), 2019)
Environment sanitation was closely related to clean and health living behavior of society to keep cleanliness and health of surrounding environment. The failure of environment sanitation affected to incident of disaster and disease epidemic which was an indirect factor of neonatal death. This research aimed to analyze the effects of environment sanitation to the incident of early neonatal death (0-7 days) in Situbondo District. This research was categorized into descriptive analytic research which exerted case control approach. The population size was 206 respondents, while the sample size was 170 respondents, selected using simple random sampling. The sample was comprised of case group of 85 mothers whose babies died in the age (0-7 days) and the control group of 85 mothers whose babies alive in the age 0-28 days. Data were analyzed using logistic regression test. This research findings showed that it was found relationship between the waste water disposal and early neonatal death, with p-value of 0.091. Keywords: environment sanitation; early neonatal deat